If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(6 + 5x) = 102 (6 * 2 + 5x * 2) = 102 (12 + 10x) = 102 Solving 12 + 10x = 102 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 10x = 102 + -12 Combine like terms: 12 + -12 = 0 0 + 10x = 102 + -12 10x = 102 + -12 Combine like terms: 102 + -12 = 90 10x = 90 Divide each side by '10'. x = 9 Simplifying x = 9
| 4x=81+x | | -29x+6.1=-5(5.8x+2.2)-0.3 | | a+0.05a= | | -45x-1=9(-5x+1)-4 | | -15=5x+10 | | (x+3)(x-4)=-12 | | (2x+3)(6-3x)=0 | | (-8x+8)2=4 | | (50-2x)*(25x+400)=204000 | | 34x+23.4=4(8.5x+4.1)+7 | | 7x+4y=4 | | -10x+17=-2(5x-5)+7 | | lnx+2+lnx+2=6 | | 2x-7=-14 | | log[5]5=x | | x*log[5](x)=18 | | (25k^2)=30 | | F(x+3)=x^2+kx-21 | | x^3+4x^2-19+14=0 | | x*(x-7)=228 | | =sin(9x) | | y=sin(9*x) | | 4[5x+5]=180 | | 3[5x+5]=75 | | 55=5[3x-4] | | -8x^2+16+x^4=0 | | 5[4x-3]=145 | | 236=4[7x+3] | | 7[3x-2]=70 | | 7[3x+3]=126 | | 180=6[4x+2] | | 6[7x-8]=246 |